O volatiloma da manipueira controla Meloidogyne javanica - Souza, Simone Ribeiro (2021)
Cassava, a liquid residue from starch plants, is known for its nematicidal activity. However, the action against the nematode of several of its volatile components is still unknown. In this study, the volatile organic compounds (VOCs) of manipueira volatiloma and their toxic effects on Meloidogyne javanica were characterized. For this, the Supelco® tube technique was used, in which sterilized sand, 20 mL of manipueira and a micro tube partially buried in the sand were placed. The tube was sealed and, after three days, an aqueous suspension containing 200 second-stage juveniles (J2) of the nematode was placed in the micro tube using a syringe. After 48 hours, it was observed that VOCs emitted by manipueira caused ~88% of J2 mortality. When J2 exposed to cassava VOCs were inoculated into tomato plants, the nematode reproduction factor was 0.37. According to analysis by chromatography coupled to mass spectrometry, in manipueira volatiloma there were eight VOCs, among which ethyl butanoate and butanoic acid stood out, which, in vitro, presented a lethal concentration of 50% (LC50) of J2 equal to ~270 μg mL-1and 176 μg mL-1, respectively. In tomato plants grown in substrate previously inoculated with nematode eggs and treated with Basamid (0.25g) and ethyl butanoate (500 or 1000 μL) no eggs were found 45 days after transplanting the tomato plants to the substrate. Although less efficient, butanoic acid (500 or 1000 μL) significantly reduced the number of galls and eggs on tomato plants when compared to the water control.